Using a continuous riverscape survey to examine the effects of the spatial structure of functional habitats on fish distribution. Issue 1 (2nd January 2016) - Pichon, Céline Le; Tales, Évelyne; Gorges, Guillaume; Baudry, Jacques; Boët, Philippe
Abstract : To fill the gap between microhabitat and landscape scale habitat models for freshwater fish, it is becoming increasingly common practice to adopt a continuous view of riverscapes, thus allowing a better understanding of the processes in place at the river management level (segments of 1–100 km). The aim of this study was to test the effects of the spatial structure of habitat on fish distribution at this scale. Inferred habitat relationships were generated using spatial metrics adapted from landscape ecology. These were calculated for two species of multi-habitat cyprinid fish in a 25-km long segment of the Seine River. A spatially continuous survey was then designed to acquire fish sampling data relating to the riverscape. Explanatory models were devised to quantify the extent to which environmental and spatial variables could describe fish distribution patterns. Spatially continuous sampling of feeding habitats at dawn and dusk provided greater understanding of the spatial distribution of common barbel ( Barbus barbus, L.) and nase ( Chondrostoma nasus, L.). Fish observations were aggregated longitudinally in neighboring feeding habitat patches, with the highest abundance found in patches with the best local conditions. The species were present for large feeding patches, as well as for a higher proximity index for those patches. This result emphasized the importance of the supplementation of feeding habitats. By quantifying spatial habitat relationships using spatial metrics, it was possible to identify the best suited configuration of functional habitats to the needs of shoals. At present, most conservation work focuses on restoring local habitats. There is also growing interest in large-scale fish management, which has been encouraged by the advent of metapopulation theory. This study highlights the need for greater work at a third, intermediate scale that is no less significant: restoring daily and seasonal movements between functional habitats.